Breastfeeding children with cleft lip and/or palate - Galvão, Dulce Maria Pereira Garcia (2014)
Introduction:Cleft lip and/or palate occur between the 4th and 9th gestation week. It may affect, totally or partially, the lip, alveolar ridge and anterior and/or posterior palate. Breastfeeding, with its known, proven and unquestionable benefits, is possible with these children. Objectives:Knowing the breastfeeding reality for children with cleft lip and/or palate and their mothers, identifying breastfeeding promoting strategies developed by nurses, knowing if the cleft type interferes with the duration and type of breastfeeding and identifying difficulties felt by the mothers. Methods:Systematic review of full text studies, published from January 2000 to April 2014, that included how it is to breastfeed these children, breastfed children with cleft lip and/or palate but with no other malformation and/or pathologies, mothers of children with cleft lip and/or palate that have breastfed; consulting CINAHL, MEDLINE, MedicLatina and Psychology and Behavioral Sciences Collection, Scholar Google, using "Cleft lip", "Cleft palate", "Child*", "Breastfeeding", "Mother", "Experience". 679 articles have been identified, 13 selected and eight used. Results:Children with cleft palate have more difficulty during breastfeed. The exclusive and total maternal breastfeeding occurred mostly on children with pre-incisive foramen cleft. The biggest difficulties were: sucking, swallowing, choking and nasal reflux. Insufficient sucking was the main cause for natural breastfeed substitution. The lack of knowledge of the health professionals regarding these babies' feeding caused the mothers not to breastfeed. They've shown concerns for the baby breathing, swallowing difficulties, colic, nasal reflux and choking. Conclusion:The breastfeeding of these children should be promoted by nurses.